An Efficient Strategy for Obtaining Mutants by Targeted Gene Deletion in Ophiostoma novo-ulmi - Sarmiento-Villamil, Jorge Luis; de Oliveira, Thais Campos; Naruzawa, Erika Sayuri; Bernier, Louis (Frontiers in Microbiology, 2021)
The dimorphic fungus Ophiostoma novo-ulmi is the highly aggressive pathogen responsible for the current, highly destructive, pandemic of Dutch elm disease (DED). Genome and transcriptome analyses of this pathogen previously revealed that a large set of genes expressed during dimorphic transition were also potentially related to plant infection processes, which seem to be regulated by molecular mechanisms different from those described in other dimorphic pathogens. Then, O. novo-ulmi can be used as a representative species to study the lifestyle of dimorphic pathogenic fungi that are not shared by the ‘‘model species’’ Candida albicans and Ustilago maydis. In order to gain better knowledge of molecular aspects underlying infection process and symptom induction by dimorphic fungi that cause vascular wilt disease, we developed a high-throughput gene deletion protocol for O. novo-ulmi. The protocol is based on transforming a Δmus52 O. novo-ulmi mutant impaired for non-homologous end joining (NHEJ) as the recipient strain, and transforming this strain with the latest version of OSCAR plasmids. The latter are used for generating deletion constructs containing the toxin-coding HSVtk gene which prevents ectopic integration of the T-DNA in Ophiostoma DNA. The frequency of gene deletion by homologous recombination (HR) at the ade1 locus associated with purine nucleotide biosynthesis was up to 77.8% in the Δmus52 mutant compared to 2% in the wild type. To validate the high efficiency of our deletion gene methodology we deleted ade7, which also belongs to the purine nucleotide pathway, as well as bct2, ogf1 and opf2 which encode fungal binuclear transcription factors. The frequency of gene replacement by HR for these genes reached up to 94%. We expect that our methodology combining the use of NHEJ deficient strains and OSCAR plasmids will function with similar high efficiencies for other O. novo-ulmi genes and other filamentous fungi.